Fintiamin: A diketopiperazine from the marine sponge‐derived fungus Eurotium sp. Issue 11 (8th August 2021) - Elsebai, Mahmoud F.; Schoeder, Clara T.; Müller, Christa E.
Abstract: The fungus Eurotium sp., derived from the marine sponge Ircinia variabilis, was found to produce a diketopiperazine–indole alkaloid that we named fintiamin (1 ). Structural elucidation of 1 was achieved by extensive spectroscopic analysis including nuclear magnetic resonance spectroscopy and mass spectrometry. Compound 1 is a lipophilic terpenoid–dipeptide hybrid molecule that shows affinity for the cannabinoid CB1 receptor at low micromolar concentrations. Docking studies based on previous X‐ray structures provide a plausible binding pose for compound 1 in the orthosteric binding site of the CB1 receptor. Abstract : Fintiamin (1 ), a diketopiperazine from the fungus Eurotium sp., is a lipophilic terpenoid–dipeptide hybrid molecule that shows affinity for the cannabinoid CB1 receptor at low micromolar concentrations. Docking studies based on previous X‐ray structures provide a plausible binding pose for compound 1 in the orthosteric binding site of the CB1 receptor.